oeis.org

A124174 - OEIS

0, 1, 10, 45, 351, 1540, 11935, 52326, 405450, 1777555, 13773376, 60384555, 467889345, 2051297326, 15894464365, 69683724540, 539943899076, 2367195337045, 18342198104230, 80414957735001, 623094791644755, 2731741367653000, 21166880717817451, 92798791542467010

COMMENTS

Sophie Germain triangular numbers are one of an infinite number of triangular number sets tr where 2*tn^2*tr + tn is a triangular number: tr and tn both also being triangular numbers with tn being held constant. For the present numbers, a(n) = tr, 8*(2*tr + 1) + 1 = 16*tr + 9 is also a square, the square root of which is 2*y+1 with y being the argument of the triangular number 2*tr + 1. Now (1/2)*(y^2+y) = a^2 + a + 1 from the definition of Sophie Germain triangular numbers. Multiply both sides by 4 and subtract 3 to get 2*y^2 + 2*y - 3 = 4*a^2 + 4*a + 1 (a square). Cf. A124124: Numbers y such that 2*y^2 + 2*y - 3 is a square. The values y are the same y such that 2*y+1 = sqrt(16*tr + 9). - Kenneth J Ramsey, Jun 25 2011

Values of k such that 2*k+1 and 9*k+1 are both triangular numbers. - Colin Barker, Jun 29 2016

FORMULA

a(n) = 35*(a(n-2) - a(n-4)) + a(n-6).

From Peter Pein, Dec 04 2006: (Start)

a(n) = -11/32 + (-3 - 2*sqrt(2))^n/64 + (5*(3 - 2*sqrt(2))^n)/32 + (-3 - 2*sqrt(2))^n/(32*sqrt(2)) - (5*(3 - 2*sqrt(2))^n)/(32*sqrt(2)) + (-3 + 2*sqrt(2))^n/64 - (-3 + 2*sqrt(2))^n/(32*sqrt(2)) + (5*(3 + 2*sqrt(2))^n)/32 + (5*(3 + 2*sqrt(2))^n)/(32*sqrt(2));

O.g.f.: (x*(1 + 9*x + x^2))/((1 - x)*(1 - 6*x + x^2)*(1 + 6*x + x^2));

E.g.f.: (-22*exp(x) + exp(-3*x+2*x*sqrt(2))*(1-sqrt(2)) - 5*exp(3*x-2*x*sqrt(2))*(-2 + sqrt(2)) + exp(-3*x-2*x*sqrt(2))*(1+sqrt(2)) + 5*exp(3*x+2*x*sqrt(2))*(2+sqrt(2)))/64. (End)

a(n) = a(n-1) + 34*a(n-2) - 34*a(n-3) - a(n-4) + a(n-5) with a(0)=0, a(1)=1, a(2)=10, a(3)=45, a(4)=351. - Harvey P. Dale, Sep 28 2011

a(n) = x*(x + 1)/2 where x = A216134(n) = (2*A000129(n) + (-1)^n*(A000129(2*floor(n/2) - 1) - (-1)^n)/2). - Raphie Frank, Jan 04 2013

a(n+2) = 1/2*((3/2*sqrt(8*a(n) + 1) + sqrt(16*a(n) + 9) - 1/2)*(3/2*sqrt(8*a(n) + 1) + sqrt(16*a(n) + 9) + 1/2)); a(0) = 0, a(1) = 1. - Raphie Frank, Jan 29 2013

MAPLE

a:= n-> (Matrix([[10, 1, 0, 0, 1]]). Matrix(5, (i, j)-> if i=j-1 then 1 elif j=1 then [1, 34, -34, -1, 1][i] else 0 fi)^n)[1, 4]: seq(a(n), n=1..30); # Alois P. Heinz, Apr 27 2009

MATHEMATICA

LinearRecurrence[{1, 34, -34, -1, 1}, {0, 1, 10, 45, 351}, 30] (* Harvey P. Dale, Sep 28 2011 *)

PROG

(Magma) I:=[0, 1, 10, 45]; [n le 4 select I[n] else 34*Self(n-2)-Self(n-4)+11: n in [1..30]]; // Vincenzo Librandi, Sep 29 2011

(PARI) a=[0, 1, 10, 45, 351]; for(n=5, 20, a=concat(a, a[#a]+34*a[#a-1]- 34*a[#a-2]-a[#a-3]+a[#a-4])); a \\ Charles R Greathouse IV, Sep 29 2011